Red Tides - Jorge R. Rey (EDIS)
ENY-851, a 5-page illustrated factsheet by Jorge R. Rey, explains what these “harmful algal blooms” are, what causes them, their impacts on marine ecosystems, human health, and coastal economies, and strategies for mitigation and control. Includes references. Published by UF Entomology and Nematology Department, February 2008.